Status of pepper farming and flower composition of different pepper varieties in Sarawak - Noorasmah Saupi (2022)
Pepper (Piper nigrum L.) is one of the most important cash crops in Sarawak. The productivity of pepper is consistently low due to the low yield of berry production. One of the major problems of pepper production is inconsistent flowering time. This is due to the morphology and inheritance of functional male, female and hermaphrodite (bisexual) flower in P. nigrum which affect the productivity of pepper. For the exploitation of pepper for its maximum production, the detailed of flower development and flower composition are important factors to be considered. A field survey was conducted to determine the status of farming practices and problems encountered by the farmers. The study was also done to determine the composition of flower which influenced the consistency of berry production in P. nigrum in Sarawak. Surveys were conducted at 18 pepper farms in Sarawak to determine the composition of flowers in different types of Sarawak pepper varieties which are Kuching, Semenggok Aman and Semenggok Emas. Nine spikes were harvested in each pepper vine. Three pepper vines were selected randomly for each variety. The spikes were then observed under 3D Keyence microscope to determine the number of flowers of each type of flower. The survey on the farming practices were also conducted. The composition of flower was found to be varied between varieties. ‘Kuching’ variety had less hermaphrodite flower when compared to ‘Semenggok Aman’ and ‘Semenggok Emas’ varieties. In addition, a proportion of 29% farmers had encountered root rot disease problem in their farm, while 21% stated that unsynchronisation of berries production in each harvesting time as a major problem.